Lucio Phenomenon With Secondary Pseudomonas Aeruginosa Infection: One Rare Case Report - Zilpa Widyastuti; Nur M. Rachmat Mulianto (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: Lucio phenomenon (LP) is a rare type of leprosy reaction. Lesions may begin as erythematous patches then progress to necrosis and leave fibrotic tissue. Secondary bacterial infection is common in patients with LP The organism that is commonly found is Pseudomonas aeruginosa which also found in this case. Case: A 57-year-old woman came with complaints of black and painful wounds on hands and feet since 8 weeks ago. Bilateral madarosis, saddle nose, and infiltration on auricularis region dextra-et-sinistra were found in facial examination. Multiple ulcers with a firmly bordered, irregular edge, erythem base, partially accompanied by necrotic tissue, slough, blood, pus and granulation were found in extremities examination. The chosen management are multibacillary multi-drug-therapy (MB MDT), methylprednisolone, and amikacin. The wounds were treated with NaCl and mupirocin ointment. Discussion: The main risk factor of LP is neglected leprosy infection. Secondary infection on LP is common. Management of LP with secondary infection consists of MB MDT and antibiotic base on the underlying bacterial infection. Conclusion: Lucio phenomenon is a rare severe type reaction of leprosy and associated with disability. Lucio phenomenon can occur before, during and after a complete MDT regimen. Systemic antibiotics are usually needed to treat LP with secondary infection.